2015
DOI: 10.2139/ssrn.2625564
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Information for Energy Efficiency in the Residential Sector

Abstract: In spite of the large potential and existing efforts to foster energy efficiency in the residential sector, much remains to be achieved. This may be partially due to the many barriers and market failures faced by energy efficiency, which are even greater in the residential sector. In particular, informational failures seem to be pervasive and relevant in this area. Addressing these issues requires specific policy instruments and strategies. This paper reviews the empirical evidence on the effectiveness of such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 136 publications
0
17
0
Order By: Relevance
“…Differences in social norms (Allcott and Rogers, 2014) and cultural and ideological factors (Ramos et al, 2015) can explain differences in environmental concern at the societal level. Table 4.…”
Section: Cross-country Comparisonmentioning
confidence: 99%
“…Differences in social norms (Allcott and Rogers, 2014) and cultural and ideological factors (Ramos et al, 2015) can explain differences in environmental concern at the societal level. Table 4.…”
Section: Cross-country Comparisonmentioning
confidence: 99%
“…Instead, researchers argue that the discussion of behavior should be guided by the social context of habits, occupant motives, and attitudes (86). Measures aimed at habits, such as information disclosure and feedback on energy consumption (particularly through smart meters) can result in substantial household energy savings (86)(87)(88)(89). The framing of the problem also affects the types of policies proposed, and there is an increasing need to integrate engineering, economic, and behavioral perspectives for effective policy (90-93).…”
Section: Buildingsmentioning
confidence: 99%
“…Most plant-based foodstuffs have substantially lower GHG emissions than animal products (96), although there are exceptions, for example, vegetables grown in heated greenhouses or fruits transported by airfreight (87). GHG benefits of plant-based food over animal products also hold when compared per unit of protein (103).…”
Section: Figurementioning
confidence: 99%
“…Several lines of evidence suggest that households tend to underinvest in energy efficiency because the negative externalities of energy use (i.e. environmental pollution and health costs) are not sufficiently internalised in energy prices, keeping energy prices too low (Allcott & Greenstone, 2012;Gerarden et al, 2015;Ramos et al, 2015). It has been further argued that the lack of information about energy-efficient technology and the own energy consumption might detain households of investing in energy efficiency (Allcott & Rogers, 2014;Group, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The importance of energy efficiency investments for the reduction of energy usage in residential buildings is well established, and yet, the uptake of energy-efficient technologies remains moderate (Ramos et al, 2015). While existing research has recognised the critical role of market barriers for the observed reluctance, such as informational and capital constraints (Gerarden et al, 2015;Jaffe & Stavins, 1994), possible behavioural explanations are still relatively unexplored (Stern et al, 2016).…”
Section: Introductionmentioning
confidence: 99%